Pattern and Consequences of Non-Replacement of Missing Teeth amongst Edentulous Adults in Ngaoundéré-Cameroon. - Agbor, Ashu Michael; Bruno, kaptue; Salomon, Zing; Ananfack, Guy Claudio; Tchweguem , Clement (British Journal of Healthcare and Medical Research, 2022)
Loss of teeth like the loss of any part of the body may affect a patient psychosocially as well as their quality of life. The objective of our study was to determine the consequences of non-replacement of missing teeth among edentulous adults in Ngaoundéré - Cameroon. This was a descriptive cross-sectional study conducted in the city of Ngaoundéré in Northern Cameroon. Data collection was done door-to-door using a questionnaire followed by oral examination. A total of 15 000 people aged between 15-98 years with a mean age of 42.5 years ±15.5 s.d were recruited for the study. . A total of 402 people were edentulous and the frequency of partial tooth loss in the community was 4.3% and the total tooth loss was 0.3%, affecting 246 (61.19%) women and 156 (38.81%) men. A third 37.81% had never consulted a dentist due to lack of finances and 86.67% consulted a dentist due to pain. Dental caries 66.43% and periodontal disease 26.89% were the main cause of tooth loss. Two-thirds 67.58% did not know that the absence of a tooth had harmful consequences. Kennedy-Applegate class III was the most represented. Total edentulism was more represented in women with dominance for the upper maxillary arch. The major consequences of tooth loss were mesial drifting 37.23%, extrusion 36.77%, masticatory difficulties (16.18%), epigastric pain 33.66%, and TMJ problems like crepitation 17.15% and pain 7.28%. The consequences of non-replaced missing teeth were included masticatory dysfunction, poor speech, epigastric pain, mesial drifting, supra eruption, TMJ dysfunction, and poor self-esteem The study showed the low knowledge of the consequences of missing teeth on the part of our study population Oral health care workers should boost oral health education and awareness of the consequences of tooth loss so as to increase knowledge of the need for dental prostheses and the oral health-seeking behavior of the population.